A Case of Everolimus-Induced Eyelid Edema. Issue 1 (January 2018) - Schear, Matthew J.; Rodgers, Rand
Abstract : Everolimus is a newer generation mammalian target of rapamycin inhibitor approved for immunosuppressive use in a number of advanced medical conditions. The authors report a unique case of persistent eyelid edema believed to be related to the immunosuppressive therapy. The therapy was being well tolerated despite the persistent eyelid edema, so the patient underwent a bilateral upper eyelid blepharoplasty. The patient responded well with resolution of her eyelid dermatochalasis and markedly decreased edema. Everolimus-induced eyelid edema should be recognized by clinicians as a potential side effect of the medication. Surgical excision of excess eyelid tissue by blepharoplasty can be a successful way to manage this side effect. Everolimus (zortress) was initially approved as an immunosuppressive agent for renal transplantation patients.1 Approval for the treatment of subependymal giant cell astrocytomas associated with tuberous sclerosis, progressive metastatic pancreatic neuroendocrine tumors, human epidermal growth factor receptor 2 negative breast cancer in postmenopausal woman, liver transplantation patients, and well-differentiated neuroendocrine tumors of gastrointestinal or pulmonary origin has followed.2, 3 Everolimus is a derivative of sirolimus (rapamune), and similar to sirolimus acts as an inhibitor of mammalian target of rapamycin.1 Few prior studies have reported eyelid edema from sirolomus.4–6 Many prior medications have been implicated in eyelid edema formation.4–11 To date, periocular edema has not been reported as a side effect of everolimus. We report a patient with bilateral upper eyelid edema associated with everolimus therapy requiring surgical intervention to ameliorate the significant skin redundancy and the visual field defect. This report complies with the Declaration of Helsinki and Health Insurance Portability and Accountability Act regulations. Abstract : A case of everolimus-induced eyelid edema was successfully managed with upper eyelid blepharoplasty.